Determinants of Internal Auditor Performance through Knowledge Management with Organizational Culture as Moderating - Sulistiyanto, Fajar; Murtini, Henny (Universitas Negeri Semarang, 2018)
This study aims to analyze the influence of transformational leadership style and transactional to knowledge management with organizational culture as moderate, and direct influence of competence, motivation, and knowledge management on internal auditors performance. The population of this study is 172 BPKP auditors representative of Central Java. The minimum number of samples that can be taken based on the slovin formula is 120 auditors. Sampling technique used simple random sampling technique. Data collection used questionnaires. This research used Structural Equation Modelling (SEM) method. Hypothesis testing used SmartPLS 3.0 program. The results of this study indicate that transformational leadership has a positive effect on knowledge management. Transactional leadership has a positive effect on knowledge management. Organizational culture moderates the transformational leadership relationship to knowledge management. Organizational culture does not moderate the transactional leadership relationship to knowledge management. Competence has a positive effect on the internal auditors’ performance. Motivation has a positive affects the internal auditors’ performance. Knowledge management has a positive affects the internal auditors performance.. The conclusion of this study is the lack of attention of leaders given to the impact of organizational culture on the knowledge management.